A novel in vivo Cerenkov luminescence image‐guided surgery on primary and metastatic colorectal cancer. Issue 3 (16th December 2019) - Zhang, Zeyu; Qu, Yawei; Cao, Yu; Shi, Xiaojing; Guo, Hongbo; Zhang, Xiaojun; Zheng, Sheng; Liu, Haifeng; Hu, Zhenhua; Tian, Jie
Abstract: Intraoperative Cerenkov luminescence imaging (CLI) can effectively improve the performance of tumor surgery. Nevertheless, the existing approaches are still unsatisfying to the clinical demands of open surgery. This study develops a novel intraoperative in vivo CLI approach to investigate the potential and value of Cerenkov luminescence (CL) image‐guided surgery. A system characterized with high sensitivity (19.61 kBq mL −1 18 F‐FDG) and desirable spatial resolution (88.34 μm) is developed. CL image‐guided surgery is performed on colorectal cancer (CRC) models of mice and swine. Tumor surgery is guided by the static CL images, and the resection quality is evaluated quantitatively and contrasted with other imaging modalities exemplified by bioluminescence imaging (BLI). The in vivo results demonstrated the effectiveness of the proposed intraoperative CLI approach for removing primary and metastatic CRC. Safety of performing in vivo CL image‐guided surgery is verified as well through radiation measurements of related staffs. Overall, the developed intraoperative in vivo CLI approach can efficiently improve the cancer treatment. Abstract : This study designs a novel intraoperative in vivo Cerenkov luminescence imaging (CLI) approach to improve the performance of tumor surgery. Experiments on both mice and swine demonstrate the promising performances of this approach in colorectal cancer (CRC) surgery. The results also present the strong feasibility and safety of the intraoperative in vivo CLI to improve the performance of CRC surgery.